Sulfide induced phosphate release from iron phosphates and its potential for phosphate recovery. (15th March 2020) - Wilfert, P.; Meerdink, J.; Degaga, B.; Temmink, H.; Korving, L.; Witkamp, G.J.; Goubitz, K.; van Loosdrecht, M.C.M.
Abstract: Sulfide is frequently suggested as a tool to release and recover phosphate from iron phosphate rich waste streams, such as sewage sludge, although systematic studies on mechanisms and efficiencies are missing. Batch experiments were conducted with different synthetic iron phosphates (purchased Fe(III)P, Fe(III)P synthesized in the lab and vivianite, Fe(II)3 (PO4 )2 *8H2 O), various sewage sludges (with different molar Fe:P ratios) and sewage sludge ash. When sulfide was added to synthetic iron phosphates (molar Fe:S = 1), phosphate release was completed within 1 h with a maximum release of 92% (vivianite), 60% (purchased Fe(III)P) and 76% (synthesized Fe(III)P). In the latter experiment, rebinding of phosphate to Fe(II) decreased net phosphate release to 56%. Prior to the re-precipitation, phosphate release was very efficient (P released/S input) because it was driven by Fe(III) reduction and not by, more sulfide demanding, FeSx formation. This was confirmed in low dose sulfide experiments without significant FeSx formation. Phosphate release from vivianite was very efficient because sulfide reacts directly (1:1) with Fe(II) to form FeSx, without Fe(III) reduction. At the same time vivianite-Fe(II) is as efficient as Fe(III) in binding phosphate. From digested sewage sludge, sulfide dissolved maximally 30% of all phosphate, from the sludge with the highest iron content which was not as high as suggested in earlier studies. Sludge dewaterability (capillary suction test, 0.13 ± 0.015 g 2 (s 2 m 4 ) −1 ) dropped significantly after sulfide addition (0.06 ± 0.004 g 2 (s 2 m 4 ) −1 ). Insignificant net phosphate release (1.5%) was observed from sewage sludge ash. Overall, sulfide can be a useful tool to release and recover phosphate bound to iron from sewage sludge. Drawbacks -deterioration of the dewaterability and a net phosphate release that is lower than expected-need to be investigated. Highlights: Sulfide releases phosphate from ferric/ferrous iron phosphate compounds. The mechanisms and efficiency of phosphate release depends on the type of iron phosphate. Sulfide is mobilizing phosphate from sewage sludges. Sulfide is a highly potential tool for phosphate recovery from sludge. Diminished sludge dewatering and phosphate mobilization below expectations are drawbacks.